Material lúdico para la enseñanza aprendizaje de matemáticas en los estudiantes con discalculia de 4to grado de la Unidad Educativa Divino Niño periodo 2021 - Erraez Solano, Ligia Rosaura; Roldan Punin, Mailyn Mayensi (Machala : Universidad Técnica de Machala, 2022)
This research work is motivated by the updated search for relevant information on playful materials for teaching and learning mathematics, which responds to a systematized quantitative-qualitative approach through the induction-deduction and analysis-synthesis method. For data collection, the observation and survey instruments were applied to determine the degree that the problem infers in the population selected for the development of the research. The methodology is oriented in response to the type of recreational material used by the teacher, advantages and appropriate materials for teaching mathematics in students with dyscalculia, in this sense, the research has the purpose of determining its application, because the teacher You must take into account that the playful material is attractive to the student, facilitates the understanding of mathematical concepts, problem solving and encourages creativity. The difficulties presented by students with dyscalculia are: recognizing and naming numbers, understanding the meaning of numerical symbols, performing mental calculations, performing mental calculations, solving problems, interpreting, reading, writing, ordering numbers, and activities related to logical thinking. abstract. Children with dyscalculia can learn to perform calculations, but they require specialized teaching and greater dedication on the part of teachers, it should be noted that this difficulty can affect any student regardless of their age or level of intelligence, it is important to recognize the difficulties that can occur in children and be prepared to help them overcome these barriers. The findings show that the playful material is rarely used, in the classroom printed material and permanent materials are sometimes used, in fact, the use of the blackboard is the greatest source for the teaching of mathematics, so there is no motivation in the student and he becomes a passive entity, recipient of content without greater relevance for reflection and argumentation for the resolution of silver exercises based on daily life in relation to abstract content. It should be noted that the teacher recognizes the advantages of playful material which favor learning, creativity, socialization and concentration, but it turns out that the educational institution does not have enough resources for its implementation, so they need to teach with what is available. The responses given by the respondents are varied, which indicates that there are different points of view regarding the use of recreational materials in 4th grade students of the Divino Niño Educational Unit. Mathematics is a subject that often generates interest in students, the use of printed and permanent material is recommended for teaching, since through its use the student reviews the theory and takes notes of the activities, but the playful material is more important to achieve effective learning due to its significant impact on academic performance, in addition to proper guidance and the use of current content, so the strengths offered by the application of playful material in the teaching-learning process of mathematics are recognizable .
El presente trabajo de investigación está motivado en la búsqueda actualizada de información relevante sobre los materiales lúdicos para la enseñanza aprendizaje de las Matemáticas, el cual responde a un enfoque cuanti-cualitativo sistematizado a través del método inducción-deducción y análisis-síntesis. Para la recolección de datos, se aplicó los instrumentos de observación y encuesta para determinar el grado que infiere la problemática en la población seleccionada para el desarrollo de la investigación. La metodología está orientada en respuesta al tipo de material lúdico que utiliza el docente, ventajas y materiales adecuados para la enseñanza de la matemática en estudiantes con discalculia, en este sentido, la investigación tiene el propósito de determinar su aplicación, debido a que el docente debe tener en cuenta que el material lúdico es atractivo para el estudiante, facilita la comprensión de los conceptos matemáticos, resolución de problemas y favorecimiento de la creatividad. Las dificultades que presentan los estudiantes con discalculia son, reconocer y nombrar números, comprender el significado de los símbolos numéricos, realizar cálculos mentales, realizar cálculos mentales, resolver problemas, interpretar, leer, escribir, ordenar números, y actividades relacionadas al pensamiento lógico-abstracto. Los niños con discalculia pueden aprender a realizar cálculos, pero requieren una enseñanza especializada y mayor dedicación por parte de los docentes, cabe resaltar, que esta dificultad puede afectar a cualquier estudiante independientemente de su edad o nivel de inteligencia, es importante reconocer las dificultades que se puedan presentar en los niños y estar preparados para ayudarlos a superar estas barreras. Los hallazgos permiten demostrar que el material lúdico es utilizado en pocas ocasiones, en el aula a veces se usa el material impreso y los materiales permanentes, en realidad, la utilización del pizarrón es la mayor fuente para la enseñanza de las Matemáticas, por lo que no hay motivación en el estudiante y se vuelve un ente pasivo, receptor de contenidos sin mayor relevancia para la reflexión y argumentación para la resolución de ejercicios plateados en base a la vida cotidiana en relación a los contenidos abstractos. Hay que destacar, que el docente reconoce las ventajas del material lúdico los cuales favorecen el aprendizaje, creatividad, socialización y concentración, pero la institución educativa beneficiaria no cuenta con los suficientes recursos para su implementación por lo que requieren enseñar con lo disponible. Las respuestas dada por los encuestados son variadas, lo cual indica que existen diversos puntos de vista en cuanto a la utilización de los materiales lúdicos en estudiantes de 4to grado de la Institución Educativa Divino Niño. Las Matemáticas es una asignatura que a menudo genera interés en los estudiantes, el uso de material impreso y el permanente es recomendable para enseñanza, ya que mediante su uso el estudiante repasa la teoría y toma apuntes de las actividades, pero el material lúdico es más importante para lograr un aprendizaje eficaz por su impacto significativo en el rendimiento académico, además de la orientación adecuada y el uso de contenidos actuales, por lo que son notables las fortalezas que ofrece la aplicación del material lúdico en el proceso de enseñanza aprendizaje de las Matemáticas.
Keywords: MATERIAL LUDICO; ENSEÑANZA APRENDIZAJE; MATEMATICA; DISCALCULIA